Antimicrobial Activity of Thiamphenicol-glycinate-acetylcysteinate and Other Drugs against Chlamydia pneumoniae - Lombardi, Alessandra; Drago, Lorenzo; Vecchi, Elena De; Mombelli, Barbara; Gismondo, Maria Rita (Arzneimittelforschung, 2001)
Chlamydia pneumoniae is responsible for respiratory tract infections of both upper and lower respiratory tract. Although this bacterium is one of the most widespread pathogens of man, there are limited data on the antibiotic treatment of C. pneumoniae infections. The aim of this study has been to evaluate the in vitro activity of thiamphenicol glycinate acetylcysteinate (TGA, CAS 20192-91-0) in comparison with molecules with established activity against C. pneumoniae, as well as macrolides and quinolones.The results have shown that TGA and clarithromycin (CAS 81103-11-9) are the most active drugs tested, but it is important to underline that the minimal inhibitory concentration (MIC) ranges of TGA are very much lower than the breakpoint of thiamphenicol for the respiratory pathogens. In conclusion, the good antimicrobial in vitro activity of TGA against C. pneumoniae together with its in vivo characteristics, in particular the high concentration reached in lung and the combination with the mucolytic agent N-acetylcysteine (NAC, CAS 616-91-1), can make a valid choice in the treatment of respiratory tract infections caused by C. pneumoniae. These findings need further evaluation by clinical studies.
Keywords: Antimicrobial susceptibility; CAS 81103-11-9; Chlamydia pneumoniae; Chloramphenicol; Respiratory tract infections; Thiamphenicol glycinate acetylcysteinate